Perancangan Aplikasi E-Learning Pada Sekolah Menengah Kejuruan - Dameyanti Saragi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The learning process in the era of developing information and communication technology (ICT) like today allows the absence of teachers in the classroom. The learning process no longer depends on teachers as the only source of learning, and can take place anytime and anywhere. The learning process is no longer just in the form of verbal communication between teachers and students. With the rapid development of information and communication technology in the world of education, with the internet as an integral part of it, many educational institutions offer web-based learning, or what is often called online learning or e-Learning. This type of learning certainly requires good and maximum management, so that learning objectives can be achieved. With all the convenience and advantages provided by the e-Learning application, hopefully this will not be interpreted as eliminating or replacing the role of a teacher in learning. It should be understood that internet technology only acts as a medium that if utilized in learning will help a lot, but the use of technology in the learning process cannot take over the entire role of a teacher. It must also be realized that the main key in the learning process is still education itself, which contains interactions, both teachers and students and students with students. e-Learning can also shorten the target learning time schedule, and of course save costs that must be incurred by an educational program. e-Learning is one form of learning method that is perceived as online. The use of e-Learning is expected to motivate improving the quality of education in Indonesia